Case 3839: Helix unidentata Draparnaud, 1805 (currently Petasina unidentata; Gastropoda, Hygromiidae): proposed conservation of the specific name and proposed fixation of the type species of the genus-group name Petasina Beck, 1847 - Hausdorf, Bernhard (Bulletin of Zoological Nomenclature, 2021)
This application has two purposes. The first, under Article 23.9.5 of the Code, is to conserve the specific name of the binomen Helix unidentata Draparnaud, 1805, a junior primary homonym of Helix unidentata Holten, 1802, by ruling that the former is not thereby invalid. These names are currently in use for two different species of stylommatophoran snails that have not been treated as congeneric since 1898. Helix unidentata Draparnaud, 1805 has been considered the type species of Petasina Beck, 1847 (Helicoidea, Hygromiidae,) by a majority of authors, whereas Helix unidentata Holten, 1802 is the valid name of Helix ventricosa De Cristofori & Jan, 1832, the type species of Stylodonta De Cristofori & Jan, 1832 (Acavidae, Rhytidoidea). The second purpose of this application, under Art. 81.1 of the Code, is to clarify the status of Petasina Beck, 1847 by (a) fixing Helix unidentata Draparnaud, 1805 as its type species and (b) confirming that Petasina Beck, 1847 is an available name independent of Petasia Beck, 1837. This is necessary to maintain current usage of not only Petasina Beck, 1847 but also another frequently used genus-group name, Euconulus Reinhardt, 1883 (Euconulidae, Trochomorphoidea). Finally, lectotypes are designated for Helix unidentata Draparnaud, 1805 and Helix edentula Draparnaud, 1805.
Keywords: Nomenclature; taxonomy; homonymy; lectotype designation; Gastropoda; Stylommatophora; Acavidae; Euconulidae; HYGROMIIDAE; Euconulus; Petasia; Petasiella; Petasina; Stylodonta; Petasina unidentata; Stylodonta unidentata; Edentiella edentula; Europe